STUDY KASUS ANALISA SCOURING JEMBATAN MENGGUNAKAN SOFTWARE HEC- RAS PADA JEMBATAN SILA, GODO I GODO II, OINIU. DI PROVINSI NUSA TENGGARA BARAT - , AHMAD RAMDANI SIREGAR, Dr. Hery Budianto, ST, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The bridge is a main supporting structure in connecting the grap area. A bridge should has strong specification criteria and be able to withstand any possible damage that will occur in the bridge. Scouring is one of the factors that cause damage to the bridge building, Scouring is produce naturally as part of the changes in the morphology of the river and the man-made structures. Final project has the purpose to find out the value of scouring which took place on bottom of a bridge which had scouring that utilized by the software program HEC Ras. HEC RAS can be used to know the depth of scouring the building of the bridge. During this research, the Program HEC Ras is the media tools used to find the value of scouring. The result of this research depict scouring by using HEC Ras software were much simpler. And use of HEC Ras Programs are helpful in work on designing the abutmen bridge to garrantic that will collapse will not occur.